Stress among nurses from countries variously affected by the COVID-19 pandemic - results collected in Poland and Iran - Andrzej Piotrowski; Zahra Nikkhah-Farkhani; Ryszard Makarowski (Nofer Institute of Occupational Medicine, 2021)
Background Nursing involves numerous stressful situations, such as overwork, night shifts, responsibility for the patients' health, rapid pace of work, emotional demands, contact with suffering individuals, and patients' aggressive behaviors. The SARS-CoV-2 pandemic is an additional demand on the already demanding profession. Thus, the aim of the current study was to assess the character of the relationship between overwork and subjectively experienced stress, taking into account the moderating role of contact with patients and work in facilities dedicated for COVID-19 patients, and the strategies of coping with stress, including resilience, in countries affected by the pandemic to various degrees. Material and Methods The study was carried out on 151 Iranian and 158 Polish nurses at the beginning of June 2020. The following research tools were used: the Overwork Climate Scale , the Brief COPE , the Resilience Scale , and the Perception of Stress Questionnaire . The participants were also asked about their contacts with patients infected with COVID-19, and work in facilities dedicated for such patients. Results Polish and Iranian nurses reported similar levels of overwork, but they differed with respect to the level of subjectively experienced stress and they used different coping strategies to various degrees. Contact with patients infected with COVID-19 and work in facilities dedicated for such patients also moderated the relationship between overwork climate and resilience. Conclusions Stress levels among Iranian and Polish nurses during the pandemic are different and are related to the intensity of contact with patients infected with COVID-19. Culture and context have an important impact on coping strategies which requires further studies with a multinational approach. Med Pr. 2021;72(5):457-65